2021
DOI: 10.22456/2316-2171.94980
|View full text |Cite
|
Sign up to set email alerts
|

Fragilidade, Sarcopenia E Caraterísticas Sociodemográficas De Idosos Longevos

Abstract: O objetivo deste trabalho é avaliar a prevalência de fragilidade e pré--fragilidade em idosos longevos atendidos em contexto ambulatorial,e analisar a associação entre as variáveis sociodemográficas, assíndromes da fragilidade e a sarcopenia. Optou-se por um estudode delineamento transversal e quantitativo com idosos do ambulatório de Geriatria do Instituto de Cardiologia do Distrito Federal,sendo avaliados pelo: questionário de dados sociodemográficos;questionário de autorrelato, que avalia o risco de sarcope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In general, the low income of Brazilians individuals aged 80 and over has been described in some studies ( 45 , 46 ), however, the discrepancies observed in the incomes could be explained by the region in which the studies were conducted. The studies that described long-lived people with higher income levels (2 to 3 minimum-wages) were carried out in the municipality of Marilia, a municipality in the state of São Paulo ( 47 ), in the south of state of Minas Gerais ( 48 ) and the Brazilian Federal District ( 49 ), while the studies that observed an average income of 1 minimum wage were conducted in the city of Recife, state of Pernambuco ( 50 ). The participants of the present study live in São Paulo, one of the richest states in the federation and has better health services that can contribute to better living conditions when compared to other regions of the country.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the low income of Brazilians individuals aged 80 and over has been described in some studies ( 45 , 46 ), however, the discrepancies observed in the incomes could be explained by the region in which the studies were conducted. The studies that described long-lived people with higher income levels (2 to 3 minimum-wages) were carried out in the municipality of Marilia, a municipality in the state of São Paulo ( 47 ), in the south of state of Minas Gerais ( 48 ) and the Brazilian Federal District ( 49 ), while the studies that observed an average income of 1 minimum wage were conducted in the city of Recife, state of Pernambuco ( 50 ). The participants of the present study live in São Paulo, one of the richest states in the federation and has better health services that can contribute to better living conditions when compared to other regions of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of frailty syndrome is significantly greater in the oldest old, with rates of 11.2-84.7% [5][6][7] reported in the international literature and 14.8-58.0% [8][9][10] in national studies. However, investigations in oldest old reveal that, besides more advanced age 6,9 , frailty syndrome is associated with being female 6,11 ; having no partner 12 ; high number of morbidities 13 ; presence of depressive symptoms 5,14,15 , poor physical performance 5,16 and with functional disability for performing activities of daily living (ADLs) 7,15 .…”
Section: Introductionmentioning
confidence: 99%
“…A prevalência da síndrome de fragilidade é significativamente maior entre os longevos, em pesquisas internacionais variam de 11,2% a 84,7% [5][6][7] , e, em nacionais de 14,8% a 58,0% [8][9][10] . Ademais, investigações entre longevos evidenciaram que, além do avançar da idade 6,9 , a síndrome de fragilidade está associada ao sexo feminino 6,11 ; à ausência de companheiro 12 ; ao maior número de morbidades 13 ; ao indicativo de sintomas depressivos 5,14,15 , ao menor desempenho físico 5,16 e à incapacidade funcional para realizar as atividades cotidianas 7,15 .…”
Section: Introductionunclassified